Energy Analysis of Health Center Facilities in Saudi Arabia: Influence of Building Orientation, Shading Devices, and Roof Solar Reflectance. (2015) - Alshayeb, Mohammed; Mohamed, Haider; Chang, Jae D.
Abstract: The healthcare sector is one of the Kingdom of Saudi Arabia's (KSA's) greatest consumers of electrical energy. The Ministry of Health has constructed and currently operating 60% of the healthcare facilities in the KSA. The ministry currently operates 249 general and specialist hospitals with 34, 370 beds and 2, 109 primary healthcare service centers. Recent government reports indicate a strong need for new healthcare facilities, which are expected to exceed 59, 000 beds by 2018 due to current demands as well as projected population growth. This increase in healthcare facilities will result in even greater energy consumption. The Ministry of Health has several approved completed designs of the hospitals and health centers needed to meet this demand. This study presents the impact of building orientation, window shading, and photovoltaic (PV) panel on the energy performance of one of the ministry's approved primary healthcare center designs. The results of this study will aid in improving the energy efficiency of the soon to be constructed health centers.